Dexamethasone in Multimodal Pain Management for Laparoscopic Surgery: A Prospective Analysis - Alyaa Hameed Saleh; Tuqa Abdullah Mohammed; Lina Ahmed Ridha; Nibras Sameer Hameed Al-Samahee (International Journal of Health and Medicine, 2025)
Objective: The study aimed to assess the adjuvant role of dexamethasone in multimodal analgesia to control postoperative pain for various laparoscopic surgical procedures.  Methods: From January to April 2023, a study was conducted at Baghdad Teaching Hospital involving 80 patients prepared for various laparoscopic procedures, classified as ASA grades I and II. The participants were divided into groups (A and B) of 40 patients. There were no significant differences between the groups regarding gender distribution, age, BMI, ASA grade, anesthesia duration, and surgical procedure duration. Group A comprises patients administered dexamethasone 8 mg intravenously one hour before the induction of anesthesia, whereas Group B patients received a normal saline (placebo). The analgesic effect was assessed by measuring the VAS score for each group at 1, 3, 6, and 24 hours post-discharge from the recovery room. The study also evaluated the necessity for potent analgesics among the study population in each group. Results: The study findings indicate that dexamethasone significantly reduces postoperative pain, as evidenced by lower VAS scores in patients administering dexamethasone compared to those receiving a placebo, especially at 6 and 24 hours post-transfer from the recovery room. Additionally, patients administering a placebo exhibit a significant demand for potent analgesia in contrast to the group receiving dexamethasone. Conclusion: The study indicated that a single-dose injection of dexamethasone 8 mg administered preoperatively for various laparoscopic procedures significantly decreases postoperative pain. Effective pain management promotes early recovery and shortens hospital stays, reducing staff stress and providing financial benefits to the institution. We recommend using dexamethasone as a safe and effective medication for alleviating postoperative pain.